Influence of the different nanostructures of acrylonitrile butadiene styrene/carbon nanotubes nanocomposites on laser cutting properties: Machining and chemical aspects. (May 2023) - Ghavidel, Ayub Karimzad; Lawrence, Jonathan; Moradi, Mahmoud
Highlights: A comprehensive study of the laser cutting process of ABS/CNTs nanocomposite. Investigating the chemical aspects of the laser cutting process of carbon-based nanocomposite for the first time. Evaluation the primary nanostructure of nanocomposites on the properties of its laser cutting for the first time. Abstract: Reported on in depth for the first time herein is the influence of the diverse nanostructures of acrylonitrile butadiene styrene (ABS)/multi-walled carbon nanotubes (MWCNTs) on its chemical, physical and electrical properties after laser cutting. Injection moulding was used to fabricate the nanocomposite samples in various structures with a thickness of 3 mm by adjusting temperature and pressure. The samples' nanostructures were evaluated prior to cutting with a CO2 laser. Design of experiments (DoE) by a full-factorial method used three levels laser power 45, 55 and 65 W) and the cutting velocity at three levels (4, 8 and 12 mm/s) as independent variables. The findings from this work are significant and support new theories. It was revealed different surface damage modes such as shrink holes, cracks, decomposed smithereens and sink marks. These were affected by the laser energy density criterion which means that the ratio of power to cutting velocity was the governing factor, whilst the effect of primary nanostructures was negligible. Unlike surface damage, the width of heat affected zone (HAZ) was found to depend on the thermal conductivity, which directly relates to the samples' nanostructure. Minimum HAZ was obtained at 0.45 mm for the sample with maximum thermal conductivity equal to 0.23 W/mK. Analysis of the post-laser cut surface and HAZ indicated that the MWCNTs were well dispersed with higher orientation and degrees of distribution. This, naturally, allows the inference that application of low laser energy density accounted for and governed oxidation of these regions. The results show that the nanotexture of the post-laser cut surface is completely changed in comparison with the as-moulded surface, leading to the lowest reduction in surface electrical resistivity to 3.2 kΩ for the sample produced at a temperature of 220 °C and a holding pressure of 70 bar.